Extensive and vicary violence: Urgent regulatory action for an initial implementation (Acta Judicial Journal, 2022)
The definitions of extension or / and vicarious violence are multiple, but if there is one that perfectly defines both, it is the following; the violence suffered by the child in order to destroy the other parent, in a very high percentage, in the figure of the mother. Difference between what is considered vicarious and extension violence.This casuistry of violence arises mainly from the processes of separation and divorce. In most cases it is a way of control over the woman, to subdue and bend her will. The woman / mother is panicked that her children may be attacked or killed. We could define it as the maximum degree of the process of control and abuse exercised on a woman who is a mother. It could be synthesized as the most extreme and atrocious way in which gender violence develops.The legal protection for this type of violence is not developed, as such, in a law but is spread in different articles in laws that specifically address some minimum aspects by which the protection is aimed at being ineffective and does not prevent or psychological damage to minors and the mother, nor, at the extreme of violence, murder of minorsThis research aims to provide instruments and normative proposals of an initial and urgent nature against this type of violence.
Keywords: Extensive or vicary violence, urgent regulatory action, Spanish law